PERTANGGUNGJAWABAN PIDANA BAGI PELAKU PEMBUANGAN BAYI DITINJAU DARI HUKUM PIDANA POSITIF (STUDI KASUS DI POLRESTA BARELANG) - Simangunsong, Sri Anita; Riyanto, Agus (SCIENTIA JOURNAL, 2019)
Disposal of a baby whose actions are inhumane, because they are victims of innocent children and because children are also the next generation of the nation. From this background the author is interested in lifting the title. The purpose of this paper is to know criminal liability in criminal acts of baby disposal in terms of the Law of Child Protection in accordance with Positive Criminal Law in Indonesia and what is the causal factor and the countermeasures related to crime of disposal crime. The method used by juridical empirical authors, while the data analysis method used is qualitative descriptive. From the results obtained, the Accountability of Baby Disposal Crimes is in accordance with Law Number 17 of 2016 Special Law concerning child protection, a factor often occurs because of promiscuity, young age, the economic response to the application of criminal witnesses, conclusions. Efficient, crime Crime of baby disposal must be prevented because it has a big influence on the future of the generation, prevention is not only recommended for the government which is the most important for the community itself.